VIII All-Russia GMP Conference with International Participation. "GMP: Proper Quality in Modern Conditions" - article Editorial (Разработка и регистрация лекарственных средств, 2023)
The main topics of the business program were approaches to regulating of drug circulation, industry education, interdepartmental interaction, a scientifically based approach to the drug manufacturing, licensing, ensuring compliance with the requirements of GMP rules, pharmaceutical engineering, and typical nonconformities during pharmaceutical inspections.